Evaluation of antibacterial effect of endodontic materials - Matović Ivan; Teodorović Nevenka (Serbian Medical Society - Dental Section, Belgrade, 2007)
Introduction. Due to the inability to sterilize infected root canals during cleaning and shaping, contemporary endodontic materials are expected to possess certain antibacterial effect. Aim. The aim of this study was to evaluate antibacterial effect of four contemporary endodontic materials: Acroseal, AH-Plus, Gutta Flow and Mineral Trioxide Aggregate (MTA) in vitro. Materials and Methods. Antibacterial effect of tested materials was evaluated against bacterial species Enterococcus faecalis ATCC 29212 using the agar diffusion test. Results. Based on the obtained results, it can be concluded that freshly mixed Acroseal and AH-Plus exhibited significant antibacterial effect while Gutta Flow and MTA did not present any antimicrobial potential in this study. Conclusion. Endodontic sealers tested in this study, freshly mixed Acroseal and AH-Plus, possess certain antibacterial effect whereas in solid state this effect is not present. .